The Structure of Oxygen Vacancies in the Near-Surface of Reduced CeO2 (111) Under Strain - Han, Zhong-Kang; Zhang, Lei; Liu, Meilin; Ganduglia-Pirovano, Maria Verónica; Gao, Yi (Frontiers in Chemistry, 2019)
Strain has been widely recognized as important for tuning the behavior of defects in metal oxides since properties such as defect configuration, electronic structure, excess charge localization and local atomic distortions may be affected by surface strain. In CeO2, the most widely used promoter in three-way catalysts and solid state electrolyte in fuel cells, the behaviors of oxygen vacancies and associated Ce3+ polarons are crucial in applications. Recent STM and AFM investigations as well as Density Functional Theory (DFT) calculations have indicated that in the near-surface of CeO2 (111), at low temperatures and vacancy concentrations, subsurface oxygen vacancies are more stable than surface ones, and the Ce3+ ions are next-nearest neighbors (NNN) to both types of vacancies, which can be explained by the better ability of the system to relax the lattice strain induced by vacancy formation as well as by the excess charge localization. The results also revealed that the interaction between first-neighbor vacancies is repulsive. In this work, the relative stability of surface and subsurface oxygen vacancies at the CeO2 (111) surface under in-plane strain is investigated by means of DFT+U calculations. The tensile strain favors isolated surface vacancies with next nearest neighbor (NNN) polaron configuration, whereas isolated subsurface vacancies with NN polaron configuration are energetically favored under compressive strain. In addition, the formation of both surface and subsurface dimers are favored over having corresponding isolated species under compressive strain, which implies the possibility of controlling the formation of vacancy clusters using strain. In many applications ceria is employed as a supported thin film or within a heterostructure in which ceria can be strained, and this study shows that strain can be a useful handle to tune properties of such materials.